Phytochemical analysis and botanical origin of Apis mellifera bee pollen from the municipality of Canavieiras, Bahia State, Brazil - Giuseppina Negri; Lidia Maria Ruv Carelli Barreto; Fábia Lugli Sper; Claudemir de Carvalho; Maria das Graças Ribeiro Campos (Brazilian Journal of Food Technology, 2018)
Abstract An Apis mellifera bee pollen sample from Bahia state in Brazil was studied to evaluate its botanical origin and phytochemical composition. The bee pollen sample was collected in the municipality of Canavieiras, in an area with a very high predominance of Cocos nucifera L (Aracaceae), which was identified as the major taxon (99%), thus being the possible botanical origin of this pollen. The main constituents found in the non-polar extract analysed by GC-EI-MS were saturated fatty acids and long chain esters, together with phytosterols such as ergosta-5,24(28)-dien-3-ol, campesterol and sitosterol, detected in smaller quantities. Flavonoid glycosides, as well as hydroxycinnamic acid amide derivatives were detected in the polar extract analysed by HPLC-ESI-MS/MS. The presence of flavonoid glycosides, hydroxycinnamic acid amide derivatives, fatty acids and phytosterols have been reported in many bee pollen taxa. To the best of the authors’ knowledge, this is the first study of the chemical composition of bee pollen from C. nucifera , which is cultivated for its coconut fruit.